“Reprisal” for the Golden Horde in the mid-twentieth century: The Ideological Discourse in Tatar Medieval Studies in the Light of the Decree of August 1944 - Gallyamova A.G. (Золотоордынское обозрение)
Objective: To reflect on the increasing significance of the decree of the Central Committee of the All-Union Communist Party of Bolsheviks of August 9, 1944 “About the Condition and Measures of Improving Mass-Political and Ideological Work in the Tatar Party Organization” for the development of Tatar history and culture. Research materials: This article is based on the documents from federal and republican archives, along with academic publications on the subject. Results and novelty of the research: The analysis of the development of the historiography of the Middle Ages in the Tatar ASSR and the work of Golden Horde specialists demonstrates that in post-Soviet historiography, the significance of the August 1944 Decree for the development of Tatar humanities is exaggerated. The official attempts to channel the development of the Tatar historical school were, in many respects, of the nature of formal rhetoric. Among the Tatar intelligentsia, academic discourse persisted even during the period of late Stalinism, not to mention the period of the “thaw”. This was convincingly evidenced by the unfolding in the early 1950s of the discussion taking place in the pages of the journal “Voprosy istorii” (Questions of History), and the achievements of M.G. Safargaliev, Sh.F. Mukhamedyarov, M.A. Usmanov, and A.G. Mukhamadiev in the study of Golden Horde issues. However, the work of humanities scholars was of the nature of a chamber, and it did not have a wide outreach to the public. Mass consciousness was formed by Moscow-produced textbooks, which were printed in millions of copies. The medieval history of the Tatars was presented in the form of an ominous yoke, an absolute evil. In this regard, the effectiveness of the influence of the August 1944 Decree should be associated not so much with the development of the humanities as with the formation of stereotypes in the public consciousness, in which the assessment of the Golden Horde was a negative one.